Lectures on the theory of socialist planning - Zieliński, Janusz G.; Nigerian Institute of Social and Economic Research (Ibadan : Published for the Nigerian Institute of Social and Economic Research [by] Oxford University Press, 1968)
The book is a theory on Socialist Planning. It provides English speaking-readers a basic outline for ideas and approach on socialist economy.
Cover title: On the theory of socialist planning.
"Based on a series of lectures given by the author at the Nigerian Institute of Social and Economic Research, University of Ibadan, Nigeria."
Includes bibliographical references.
osa 06/06/2018
Loans
Keywords: Socialist economy; Communist countries